PAI CURRICULUM CHANGES FROM TIME TO TIME - Fitriah Khoirul Umamah; Dzihni mutawakkil Alalloh; Nanang Budianto (International Journal of Multidisciplinary Reseach, 2026)
The Islamic Religious Education (PAI) curriculum in Indonesia has undergone significant changes since the early days of independence until the Merdeka Curriculum era. Each curriculum change reflects evolving educational needs, social dynamics, and ever-changing global challenges. This study aims to describe the development of the PAI curriculum from 1947, 1952, 1968, 1975, 1984, 1994, 2004 (KBK), 2006 (KTSP), 2013, to the Merdeka Curriculum in 2022. The method used ishistorical researchthrough an analysis of official documents from the Ministry of Education and Culture and other relevant literature. The results show that changes to the Islamic Religious Education curriculum are influenced by factors such as relevance to the times, technological advances, societal needs, demands for 21st-century competencies, and national education policies. These changes have positive impacts, such as increased learning relevance, character building, and flexibility in implementation, but also present challenges, particularly teacher readiness and adaptation of the learning system. The latest curriculum, the Merdeka Curriculum, offers a more flexible, student-centered model that emphasizes religious moderation and contextual learning. In conclusion, the development of the Islamic Religious Education curriculum over time is an adaptive process aimed at improving the quality of Islamic education to meet the needs of generations and the demands of the times